Oral tradition and communication - Aryal, Deepak (Bodhi: An Interdisciplinary Journal, 2010)
Oral tradition has become a domain of great interest to scholars of different disciplines of knowledge such as literature, psychology, anthropology, and philosophy. It has a huge scope for the discipline of communication too. This article presents an appraisal of oral tradition as a means of communication from one generation to another. While doing so, it deals with following issues: Can history be narrated based on oral traditions just as it is done with ‘written documents'? Are the oral traditions only the sources of historiography or do they have other implications too? It also discusses whether oral traditions can be taken as valid historical sources, and, if not, whether there are means for testing its reliability. DOI: 10.3126/bodhi.v3i1.2813 Bodhi Vol.3(1) 2009 p.61-68